Clinical Outcomes Following Revision Total Knee Arthroplasty for Septic vs Aseptic Indications: A Comparative Analysis With at Least 1-Year Follow-up - Yakup Doğan; Alpaslan Öztürk; Oğuz Çetin; Ali Ömer Kaya; Nazan Çevik; Yavuz Akalın; Hüseyin Yetkin (The European Research Journal, 2026)
Objective: This study aimed to retrospectively compare the clinical, functional, and radiographic outcomes of revision total knee arthroplasty (rTKA) performed for septic and aseptic indications and to evaluate postoperative changes within each group. Methods: A total of 27 patients (30 knees), including 18 females and 9 males, were included in the study. Patients were categorized into 2 groups: those who underwent rTKA due to septic loosening (13 patients, 13 knees) and those with aseptic causes (14 patients, 17 knees). Results: In the septic group, a comparison of preoperative and postoperative scores revealed significant improvements in the Oxford Knee Score (OKS), Patellar Scoring System, and Knee Society Score (KSS) for both knee and function components (P = .003, P = .004, P = .003, and P = .002, respectively). Similarly, in the aseptic group, significant improvements were observed in the OKS, Patellar Scoring System, and KSS knee and function scores when comparing preoperative and postoperative results (P < .001, P < .001, P < .001, and P = .001, respectively). Aseptic loosening was found to occur more frequently in female patients (P = .02). Flexion improved significantly in both the septic (P = .006) and aseptic (P = .001) groups, whereas significant extension gain was observed only in the aseptic group (P = .025; septic P = .102). Conclusion: In this retrospective cohort, both the septic and aseptic rTKA groups demonstrated significant postoperative improvements in clinical and functional outcomes, whereas most evaluated postoperative outcomes did not differ significantly between the groups. These findings describe the clinical and functional outcomes observed in this cohort without establishing superiority or equivalence between revision indications.